Beyond budgeting: review and research agenda. Issue 3 (7th September 2018) - Nguyen, Dai Huu; Weigel, Christine; Hiebl, Martin R.W.
Abstract : Purpose: Beyond budgeting has received an increased amount of scholarly attention in recent years. However, because most of the published research is discrete and unconnected, an overall picture of what is known about beyond budgeting has not evolved. Therefore, the purpose of this paper is to provide an overview of the available research on beyond budgeting. In particular, the authors compare conceptual papers that mostly stress the benefits of beyond budgeting with empirical evidence on beyond budgeting implementation and offer ideas for future research on beyond budgeting. Design/methodology/approach: This paper uses systematic literature review methods. After an extensive database search and examination of references/citations, 32 papers were analysed with regard to bibliographical information, research design and findings. Findings: Although proponents of beyond budgeting have put substantial effort into developing and promoting this concept, numerous empirical studies demonstrate that many organizations being investigated would still rather improve traditional budgeting than abandon it completely. This review also highlights the main criticisms of traditional budgeting, development of management control systems under beyond budgeting and factors hindering the implementation of beyond budgeting. Research limitations/implication: This paper suggests that further research is needed on the scaling of beyond budgeting, organizational changes under beyond budgeting and challenges resulting from the implementation of beyond budgeting. Originality/value: The paper is the first comprehensive literature review on beyond budgeting.